Mixing and Phytoplankton Growth in an Upwelling System - Comesaña, Antonio; Fernández-Castro, Bieito; Chouciño, Paloma; Fernández, Emilio; Fuentes-Lema, Antonio; Gilcoto, Miguel; Pérez-Lorenzo, María; Mouriño-Carballido, Beatriz (Frontiers in Marine Science, 2021)
Previous studies focused on understanding the role of physical drivers on phytoplankton bloom formation mainly used indirect estimates of turbulent mixing. Here we use weekly observations of microstructure turbulence, dissolved inorganic nutrients, chlorophyll\,a concentration and primary production carried out in the Ría de Vigo (NW Iberian upwelling system) between March 2017 and May 2018 to investigate the relationship between turbulent mixing and phytoplankton growth at different temporal scales. In order to interpret our results, we used the theoretical framework described by the Critical Turbulent Hypothesis (CTH). According to this conceptual model if turbulence is low enough, the depth of the layer where mixing is active can be shallower than the mixed-layer depth, and phytoplankton may receive enough light to bloom. Our results showed that the coupling between turbulent mixing and phytoplankton growth in this system occurs at seasonal, but also at shorter time scales. In agreement with the CTH, higher phytoplankton growth rates were observed when mixing was low during spring-summer transitional and upwelling periods, whereas low values were described during periods of high mixing (fall-winter transitional and downwelling). However, low mixing conditions were not enough to ensure phytoplankton growth, as low phytoplankton growth was also found under these circumstances. Wavelet spectral analysis revealed that turbulent mixing and phytoplankton growth were also related at shorter time scales. The higher coherence between both variables was found in spring-summer at the $\sim\!16$-$30$ d period and in fall-winter at the $\sim\!16$-$90$ d period. These results suggest that mixing could act as a control factor on phytoplankton growth over the seasonal cycle, and could be also involved in the formation of occasional short-lived phytoplankton blooms.